2019
DOI: 10.3390/electronics8040428
|View full text |Cite
|
Sign up to set email alerts
|

Open-Source Electronics Platforms: Development and Applications

Abstract: Open-source electronics are becoming very popular with our daily educational and developmental purposes [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…Finally, the system's ability to log data and monitor temperature trends in real time allows researchers and students to better understand the pyrolysis process. The low cost of manufacturing for the OS BREAD system enables it to be used in education, which is also consistent with other open-source electronics devices in the literature [63,64].…”
Section: Discussionsupporting
confidence: 78%
“…Finally, the system's ability to log data and monitor temperature trends in real time allows researchers and students to better understand the pyrolysis process. The low cost of manufacturing for the OS BREAD system enables it to be used in education, which is also consistent with other open-source electronics devices in the literature [63,64].…”
Section: Discussionsupporting
confidence: 78%
“…For example, a recent review of hundreds of published scientific open hardware found that FOSH provides economic savings of 87% compared to equivalent or lesser proprietary tools that increased to 94% for those that used open source electronics and open source 3-D printing (Pearce, 2020). The rapid technical evolution of FOSH is already clear for both the electronics industry where many commercial firms sell FOSH (Ngo, 2019;Hannig & Teich, 2021), and the additive manufacturing industry where millions of free 3-D printable designs already exist (Wittbrodt et al, 2013).…”
Section: Introductionmentioning
confidence: 99%